Histometabolic Tumor Imaging of Hypoxia in Oral Cancer: Clinicopathological Correlation for Prediction of an Aggressive Phenotype - Morand, Grégoire B.; Broglie, Martina A.; Schumann, Paul; Huellner, Martin W.; Rupp, Niels J. (Frontiers in Oncology, 2020)
Introduction Fluorodeoxyglucose-positron emission tomography (FDG-PET) is a widely used imaging tool for oral squamous cell carcinoma (OSCC). Preliminary studies indicate that quantification of tumor metabolic uptake may correlate with tumor hypoxia and aggressive phenotypes. Methods Retrospective review of a consecutive cohort of OSCC (n = 98) with available pretherapeutic FDG-PET/CT, treated at the University Hospital Zurich. Clinico-pathologico-radiological correlation between maximum standard uptake value (SUVmax) of the primary tumor, immunohistochemical staining for hypoxia-related proteins glucose transporter 1 (GLUT1) and hypoxia-inducible factor 1-alpha (HIF1a), depth of invasion (DOI), lymph node metastasis, and outcome was examined. Results Positive staining for GLUT1 and HIF1a on immunohistopathological analysis correlated with increased SUVmax on pretherapeutic imaging and with increased DOI (Kruskal–Wallis, P = 0.037, and P = 0.008, respectively). SUVmax and DOI showed a strong positive correlation (Spearman Rho, correlation coefficient = 0.451, P = 0.0003). An increase in SUVmax predicted nodal metastasis (Kruskal–Wallis, P = 0.017) and poor local control (log rank, P = 0.047). Conclusion In OSCC, FDG-PET-derived metabolic tumor parameter SUVmax serves as a surrogate marker for hypoxia and can be used to predict tumor aggressiveness, with more invasive phenotypes and poorer local control.